SISTEM INTELIJEN EVALUASI KELAYAKAN PINJAMAN USAHA KECIL MENENGAH AGROINDUSTRI OLEH PERBANKAN - Irawadi Jamaran, Anas M. Fauzi, Marimin dan Effatha G.V.G Tamburian (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACT The sustainability operation of an agroindustrial production system in a competitive global market shall be supported by capital structural elements (investment and working capital) that concern with assets, liability, and profitability of a company. Banking (conventional and syariah), as the most important financial intermediation institution of the national economic system (Arifin, 2002), has to feature small and medium enterprise (SME) in agroindustrial sector. The SME can strengthen the national economy, support the national industrial development objective, become the “back bone” of national economy, and answer important issues related with Indonesian reformation process (ADB, 2001). The feasibility study of the SME agroindustrial working capital loan that utillizes risk level concept and intelligent system method shall be done due to its complexity and uncertainty. The research aims to formulate the ANFIS structure in neuro-fuzzy system that is supported by risk level concept and feasibility study method of working capital loan worthiness evaluation, and verification.The result is a standard operating procedure (SOP) of intelligent worthiness evaluation of small and medium agroindustrial working capital loan, i.e. fuzzy inference system (FIS) and training process of fhe system. The conclusion is a model formulation process of FIS Takagi-Sugeno-Kang’s type, that integrates the training process of artifical neural network model with risk level as the parameter in regulating the rules, and weighted score in determining fuzzy score (risk level) interval. The verification indicates that to reach Accept A/clean worthiness in loan decision based on the FIS result, the evaluation of aspect judgment should be well, with the low risk level of aspect criteries (conventional and syariah banking). The result of training in FIS is the prediction of debtor condition, where the best condition is compulsory to reach commonly the low risk level towards the worthiness. The submitted sugesstion is the SOP development as an intelligent decision support system (IDSS) that shall be integrated based on neuro-fuzzy system, ANFIS and others, to reduce the limitation in steps of model implementation (resources : human, software and hardware), and has the suitable weight of the worthiness aspects Key words : Intelligent, Evaluation, Worthiness, SME, Agroindustry